RANCANG BANGUN PROTOTIPE MESIN HORIZONTAL PACKAGING BERBASIS ARDUINO UNO - Susilo, Priyo; Saleh, Agus (Jurnal Mahasiswa Terapan, 2025)
Manual packaging processes in small and medium-sized industries (SMIs) are often inefficient, time-consuming, and labor-dependent. This research aims to design an Arduino Uno-based automated horizontal packaging machine prototype capable of precisely arranging 15×7×7 cm boxes into mailer-type cartons. The research methodology includes the design of a mechanical system an electrical, and a control system programmed using Arduino Uno. Testing results show that the machine operates stably, with the GT2 synchronous belt transmission system (3:1 ratio) effectively driving the conveyor belt and shaft without slippage. The pushing unit successfully positions three boxes into the mailer box. However, the machine has limitations, including a maximum load capacity of 2 kg and dependence on limit switches, which are prone to mechanical errors. This research contributes to a low-cost automation solution for small industries, with potential for further development, such as adding proximity sensors, PID control, or IoT integration. The prototype demonstrates that Arduino Uno can serve as an effective foundation for intermediate-complexity automated packaging systems.